The scripture of the golden eternity - Kerouac, Jack, 1922-1969 (Open Road Integrated Media, 2016)
Poetic meditations on joy, consciousness, and becoming one with the infinite universe from the author of On the Road During an unexplained fainting spell, Beat Generation writer Jack Kerouac experienced a flash of enlightenment. A student of Buddhist philosophy, Kerouac recognized the experience as "satori," a moment of life-changing epiphany. The knowledge he gained in that instant is expressed in this volume of sixty-six prose poems with language that is both precise and cryptic, mystical and plain. His vision proclaims, "There are not two of us here, reader and writer, but one golden eternity." Within these meditations, haikus, and Zen koans is a contemplation of consciousness and impermanence. While heavily influenced by the form of Buddhist poems or sutras, Kerouac also draws inspiration from a variety of religious traditions, including Taoism, Native American spirituality, and the Catholicism of his youth. Far-reaching and inclusive, this collection reveals the breadth of Kerouac's poetic sensibility and the curiosity, word play, and fierce desire to understand the nature of existence that make up the foundational concepts of Beat poetry and propel all of Kerouac's writing.